CRIMINAL LIABILITY FOR ASSISTANCE TO TERRORIST ACT BY LEGISLATION OF UKRAINE AND RUSSIAN FEDERATION: COMPARATIVE ANALYSIS - N. N. Vasilin; F. M. Luchinkin (Russian Journal of Economics and Law, 2013)
The article is devoted to comparative analysis of criminal law norms stating the liability for assisting to terrorist act by legislation of the Ukraine and the Russian Federation. Basing on analysis, the authors come to the conclusion about necessity to introduce changes into the existing legislation.